2020
DOI: 10.1038/s41598-019-57026-1
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive rapid detection of metabolic adaptation in activated human T lymphocytes by hyperpolarized 13C magnetic resonance

Abstract: The metabolic shift induced in human CD4 + t lymphocytes by stimulation is characterized by an upregulation of glycolysis, leading to an augmentation in lactate production. this adaptation has already been highlighted with various techniques and reported in several previous studies. We herein propose a method to rapidly and noninvasively detect the associated increase in flux from pyruvate to lactate catalyzed by lactate dehydrogenase using hyperpolarized 13 c magnetic resonance, a technique which can be used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 44 publications
(55 reference statements)
0
16
2
Order By: Relevance
“…This effect arises because the gyromagnetic ratio of deuterium is ~7‐fold weaker than that of protium, leading to weaker dipolar interactions 30 . Previous methods of multiple‐sample spectral acquisition using a single dissolution have been limited to two 31 or three 32 independent samples. The method we present here, combining a microcoil design allowing for rapid cell suspension sample load/unload/reload capability and the extended hyperpolarized lifetime of [1‐ 13 C] pyruvate dissolved in D 2 O, enabled up to eight reproducible high‐throughput measurements of pyruvate‐to‐lactate metabolic flux in multiple independent samples using a single HP dissolution.…”
Section: Discussionmentioning
confidence: 99%
“…This effect arises because the gyromagnetic ratio of deuterium is ~7‐fold weaker than that of protium, leading to weaker dipolar interactions 30 . Previous methods of multiple‐sample spectral acquisition using a single dissolution have been limited to two 31 or three 32 independent samples. The method we present here, combining a microcoil design allowing for rapid cell suspension sample load/unload/reload capability and the extended hyperpolarized lifetime of [1‐ 13 C] pyruvate dissolved in D 2 O, enabled up to eight reproducible high‐throughput measurements of pyruvate‐to‐lactate metabolic flux in multiple independent samples using a single HP dissolution.…”
Section: Discussionmentioning
confidence: 99%
“…This metabolic signature was detectable through hyperpolarized [1‐ 13 C]pyruvate to [1‐ 13 C]lactate flux in an in vitro T cell culture 56 . As with the macrophage models, increased [1‐ 13 C]lactate (the sum of both intracellular and extracellular lactate) production was associated with increased expression of LDH and an increased lactate/pyruvate ratio in stimulated cultures compared with resting state T cells 54,56 …”
Section: Assessment Of Immunometabolic Responses By Hyperpolarized Mrmentioning
confidence: 93%
“…Activation of regulatory T cells rapidly increases their metabolic demand to sustain proliferation and function; this is largely met by upregulation of glycolysis. A recent study of soluble anti‐CD28–activated human T cells demonstrated the applicability of hyperpolarized 13 C MRS for measurements of immune cell function 56 . Stimulated regulatory T cells exhibit a similar pattern in their metabolic shift to that seen in macrophages, with an upregulation of glycolysis leading to increased lactate production 56 .…”
Section: Assessment Of Immunometabolic Responses By Hyperpolarized Mrmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this limitation 13 C-labeled metabolites detected by spectroscopic magnetic resonance imaging (MRI) have become increasingly used for functional imaging primarily in the setting of malignancy [25][26][27][28][29][30] , and more recently in other inflammatory conditions 31,32 . Ex vivo dynamic nuclear hyperpolarization (DNP) of the 13 C-pyruvate tracer prior to infusion has improved the sensitivity of its MRI detection to allow real-time spectroscopic measurement of in vivo glycolytic activity within tissues in preclinical and clinical studies 33,34 . An additional benefit of this methodology is the lack of exposure to radioactivity from the tracer and/or scanner.…”
Section: Introductionmentioning
confidence: 99%